Combining predictive distribution methods and life history to reduce geographic distribution shortfalls for two rocky Cerrado endemic leaf frogs - Del Prette, Ana Cecília Holler; Magalhães, Rafael Félix de; Lemes, Priscila; Pezzuti, Tiago Leite [UNESP]; Strüssmann, Christine; Oswald, Caroline Batistim; Oliveira, Jean Carlo Pedroso de; Santos, Fabrício Rodrigues dos; Brandão, Reuber Albuquerque (Elsevier, 2024)
Species-focused conservation requires accurate knowledge of geographic distribution to effectively categorize species in red lists, assess threats, and plan conservation initiatives. In this study, we describe a protocol used to identify potential occurrence locations for two habitat-specialist leaf frogs, Pithecopus ayeaye and P. oreades, by (1) creating species distribution models (SDMs) using climate data, and (2) utilizing natural history information to select potential occurrence points in high-resolution satellite images within high-suitable climate conditions determined in the previous step. Field validation of the protocol yielded a high success rate in discovering new populations for both species. As these species show morphological and reproductive similarities, we used molecular tools for taxonomic resolution. We documented 36 new records (22 for P. ayeaye and 14 for P. oreades). The commission error in the P. oreades SDM led to new records for P. ayeaye, indicating niche conservatism and suggesting a higher climatic tolerance than predicted by the P. ayeaye SDM. Furthermore, we identified a sympatric zone that may facilitate interspecific gene flow. Our protocol effectively addressed the Wallacean shortfall for these two species, and we propose similar approaches for predicting the potential distribution of rare species with mappable specific habitat preferences.
Keywords: Campo rupestre; Ecological niche modelling; Molecular identification; Satellite imagery; Sympatry; Wallacean shortfall